Glycyrrhetinic acid and E.resveratroloside act as potential plant derived compounds against dopamine receptor D3 for Parkinson’s disease: a pharmacoinformatics study - Mirza MU; Mirza AH; Ghori NUH; Ferdous S (Drug Design, Development and Therapy, 2014)
Muhammad Usman Mirza,1 A Hammad Mirza,2 Noor-Ul-Huda Ghori,3 Saba Ferdous4 1Centre for Research in Molecular Medicine, The University of Lahore, Lahore, Pakistan; 2Department of Bioscience, COMSATS Institute of Information Technology, Sahiwal, Pakistan; 3Atta-ur-Rehman School of Applied Biosciences, National University of Science and Technology, Islamabad, Pakistan; 4Institute of Structural and Molecular Biology, University College London, UK Abstract: Parkinson’s disease (PD) is caused by loss in nigrostriatal dopaminergic neurons and is ranked as the second most common neurodegenerative disorder. Dopamine receptor D3 is considered as a potential target in drug development against PD because of its lesser side effects and higher degree of neuro-protection. One of the prominent therapies currently available for PD is the use of dopamine agonists which mimic the natural action of dopamine in the brain and stimulate dopamine receptors directly. Unfortunately, use of these pharmacological therapies such as bromocriptine, apomorphine, and ropinirole provides only temporary relief of the disease symptoms and is frequently linked with insomnia, anxiety, depression, and agitation. Thus, there is a need for an alternative treatment that not only hinders neurodegeneration, but also has few or no side effects. Since the past decade, much attention has been given to exploitation of phytochemicals and their use in alternative medicine research. This is because plants are a cheap, indispensable, and never ending resource of active compounds that are beneficial against various diseases. In the current study, 40 active phytochemicals against PD were selected through literature survey. These ligands were docked with dopamine receptor D3 using AutoDock and AutoDockVina. Binding energies were compared to docking results of drugs approved by the US Food and Drug Administration against PD. The compounds were further analyzed for their absorption, distribution, metabolism, and excretion-toxicity profile. From the study it is concluded that glycyrrhetinic acid and E.resveratroloside are potent compounds having high binding energies which should be considered as potential lead compounds for drug development against PD. Keywords: AutoDock, AutoDockVina, molecular docking, parkinson’s disease, glycyrrhetinic acid, E.resveratroloside